The key determinants of individual greenhouse gas emissions in Germany are mostly domain-specific - Brandenstein, Nils; Ackermann, Kathrin; Aeschbach, Nicole; Rummel, Jan (Communications earth & environment, 2023)
Individual behavior plays a pivotal role in mitigating climate change but our understanding of the multifaceted, determining factors of sustainable behavior remains incomplete. Here we conducted a comprehensive, cross-sectional survey of German households in 2021 (N = 10,813), assessing various potential determinants and measuring behavior in greenhouse gas emissions across various life domains (shelter, mobility, consumption, and diet). Machine learning models were employed to predict emissions from determining factors and benchmarked against commonly used linear models. Our findings indicate that machine learning models excel in capturing complex relationships between personal and situational factors, offering a more nuanced understanding of how determinants interplay and contribute to emissions. Notably, some factors like perceived behavioral control or habits consistently affected emissions, while others like infrastructural barriers and pro-environmental attitudes were domain-specific. These insights about key determinants of sustainable behavior are valuable for policymakers crafting effective climate change strategies at the individual level.
Gesehen am 08.03.2024